Regional Workshop on Agribusiness Public-Private Partnerships in Cambodia, Lao PDR and Vietnam - Phounvisouk, L.; Sonethavixay, Sengphachanh; Inphonephong, Souphalack (International Water Management Institute (IWMI). CGIAR Initiative on National Policies and Strategies, 2024)
This report documents the regional workshop on agribusiness public-private partnership (agriPPP), organized in Luangprabang, Laos, from 15–16 March 2024, with 47 participants from Cambodia, Vietnam and Lao People Democratic Republic (Lao PDR). The event was hosted by the Policy Think Tank (PTT) initiative of the National Agriculture and Forestry Research Institute (NAFRI) of the Ministry of Agriculture and Forestry (MAF). The event was supported by a funded project of the International Fund for Agricultural Development (IFAD) and CGIAR Initiative on National Policies and Strategies (NPS) via the International Water Management Institute (IWMI).